P300 and smooth eye pursuit: concordance of abnormalities and relation to clinical features in DSM-III schizophrenia. - Ebmeier, K; Potter, D; Cochrane, R; Mackenzie, A; MacAllister, H; Besson, J; Salzen, E (1990)
Twenty-five DSM-III-diagnosed schizophrenics and 37 normal and age-matched controls were examined using an oddball paradigm for the generation of P300 and smooth eye-pursuit tasks. Results were compared between groups and related to clinical characteristics, including a family history of psychiatric illness. Group differences were found for P300 amplitudes, latencies and eye-tracking. A family history of psychiatric illness was associated with normal eye-tracking in patients. Small P300 amplitudes alone and in combination with long P300 latencies were associated with a family history in controls.